Differences in sprint profile, sprint completion times, and jumping performance between division i track and field sprinters, throwers, and long-distance runners - Dietze-Hermosa, M.; Montalvo, S.; Gonzalez, M. P.; Cubillos, N. R.; Dorgo, S. (Journal of Physical Education and Sport, 2023)
Problem Statement: The sport demands of differing track and field events may impact sprinting and jumping performance. Yet this remains to be explored across sprinters, throwers, and long-distance runners. Purpose: This study explored the differences in sprint profile measures, sprint completion times, and jump performance between track and field athletes. Approach: Forty-two collegiate track and field athletes (sprinters = 18; throwers = 10; long-distance runners = 14) completed broad jump (BJ) trials where distance and peak vertical and horizontal forces were obtained. Force, power, and modified reactive strength index were obtained during vertical countermovement jumps (VJ). Subjects completed 30-meter sprints with the MySprint mobile application assessing subjects` sprint profile including maximal theoretical horizontal force, maximal theoretical velocity, maximal theoretical power, maximal speed, maximal ratio of force, force-velocity slope, and decrease in ratio of force. A series of one-way ANOVAs with follow up comparisons determined group differences for each measure of interest. Results: Multiple sprint profile variables and sprint completion times differed between sprinters and long-distance runners (p < 0.01; Hedge`s g = 1.20 to 1.50). Similarly, sprint profile variables and sprint completion times differed between sprinters and throwers (p < 0.05; Hedge`s g = 0.97 to 1.37). Additionally, various jump performance variables during VJ, and BJ differed between sprinters and long-distance runners (p < 0.05; Hedge`s g = 1.02 to 2.18) and between sprinters and throwers (p < 0.05; Hedge`s g =1.10 to 1.90). Conclusions: Sprinters apply higher horizontally-oriented forces during sprinting compared to long-distance runners and throwers contributing to a superior sprint performance. Sprinters display better force application during jump performance compared to throwers and long-distance runners. Negligible differences exist in sprint and jump performance between throwers and long-distance runners.